2014
DOI: 10.1016/j.jacc.2013.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Computed Tomography in Patients With Cardiac Rhythm Management Devices

Abstract: The findings suggest that the presence of CRM devices should not delay or result in cancellation of clinically indicated CT imaging procedures, and provide evidence that would be helpful when the FDA advisory is re-evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Brief CT examinations have been found to be safe for patients with CIEDs. The study by Hussein et al 74 showed no strong evidence of clinical significant risks associated with direct CT irradiation of CIEDs. However, precautions may need to be taken for scans that will directly irradiate the device for longer than 3 s (e.g., 4DCT scans or perfusion imaging).…”
Section: C Simulationmentioning
confidence: 94%
See 2 more Smart Citations
“…Brief CT examinations have been found to be safe for patients with CIEDs. The study by Hussein et al 74 showed no strong evidence of clinical significant risks associated with direct CT irradiation of CIEDs. However, precautions may need to be taken for scans that will directly irradiate the device for longer than 3 s (e.g., 4DCT scans or perfusion imaging).…”
Section: C Simulationmentioning
confidence: 94%
“…Caution may be warranted when performing prolonged scans such as perfusion imaging or 4DCT to manage risk to the device. However, CT irradiation of a CIED has not shown to be a clinically significant problem . For positron emission tomography with 2‐deoxy‐2‐[fluorine‐18] fluoro‐D‐glucose integrated with CT (18F‐FDG PET/CT) scans, patients with a CIED can safely undergo the PET scan.…”
Section: Malfunction Risk Associated With Clinical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…4D CT). Bylo popsáno několik poruch v souvislosti s provozem CT, nicméně jen v případě dlouhodobějšího přímého ozáření těla přístroje s následkem nadměrné stimulace ICP a s vynecháním potřebné stimulace, případně se spouštěním antitachyarytmické léčby u ICD [27,34,35]. Krátkodobé ozáření přístroje nízkonapěťovými zdroji (v řádu keV) nejsou pro klinickou manifestaci přechodných poruch přístroje rizikové [36].…”
Section: Simulaceunclassified